225 Effect of Long-Term Administration of Tadalafil on Arteriosclerosis: A Prospective Cohort Study. (1st May 2022) - Hayashi, K; Sasaki, H; Mugita, T; Tomiyama, T; Koizumi, S; Kurokawa, I; Matsubara, E; Saito, K; Fuji, K; Ishikawa, K; Fukagai, T
ABSTRACT: Introduction: Tadalafil is a phosphodiesterase type 5 (PDE-5) inhibitor, and it is used globally as a highly effective and safe drug for the treatment of erectile dysfunction (ED) and lower urinary tract symptom (LUTS). Tadalafil relieve ED or LUTS by relaxing vascular smooth muscle and increasing blood flow to the lower urinary tract tissue. PDE is distributed in pelvic organs, including the corpus spongiosum of the penis and the urethra and prostate, as well as in the lung, heart, and vascular smooth muscle. In other words, PDE is distributed throughout the body. Thus, we hypothesized that the administration of tadalafil might reduce not only systemic arteriosclerosis but also ischemia of the lower urinary tract. Objective: To prospectively investigate whether the long-term administration of tadalafil, which is commonly used for erectile dysfunction, could reduce arteriosclerosis. Methods: This study included 85 patients who presented to one of three hospitals with lower urinary tract symptoms. Tadalafil was administered daily (5 mg/d), and pulse wave velocity was measured before administration and at weeks 12, 24, 36, and 48. The International Prostate Symptom Score, Overactive Bladder Symptom Score, and Erection Hardness Score were simultaneously assessed at the same time points. Further sub analyses were performed in patients with a high risk of cardiovascular events, those aged 75 years or older, and those younger than 75 years. The Wilcoxon signed rank test was used for statistical analysis. Results: Compared with pretreatment values, the pulse wave velocity did not show any statistically significant decrease at any time point. However, the three aforementioned scores significantly improved compared. The group at high risk of cardiovascular events showed significant improvement at weeks 24 and 36, whereas the 75 years or older group showed significant improvement at only week 24. Conclusions: The long-term administration of tadalafil (5 mg daily) reduced arteriosclerosis or inhibited its progression, and relieved dysuria and improved erectile function. In particular, the drug was revealed to be more effective in patients at a high risk of cardiovascular events and those aged 75 years or older. Hence, tadalafil may have the potential to be used as an anti-aging medicine, although further studies with longer observation periods are needed to confirm its effectiveness and safety. Disclosure: Work supported by industry: no.